KESESUAIAN TANAH TERHADAP HASIL TANAMAN KAKAO (KOPI COKLAT) DI NAGARI SIBAKUR KECAMATAN TANJUNG GADANG KABUPATEN SIJUNJUNG - Yulita, Darmiyus; Dasrizal, Dasrizal; Zahara, Leni (STKIP PGRI Sumbar, 2013)
The researched was conducted with the purposes of 1) determine the effect of land suitable for cocoa crops (coffee, chocolate). 2) determine the ones where the land suitable for cocoa crops (coffee, chocolate) in Nagari Sibakur. And samples taken only 4 units of land onlySampling technique based on determination same sample point, which represents the population of the study area. Reason retrieval with this method because they on the same land unit has assumed the same characteristics as well, so that the same unit of land form mentioned can represent by land units. Data analysis was the quantitative descriptive analysis in the form of tables of comparison between soil characteristics (texture, effective soil depth, drainage, soil pH, organic matter, and slope) compared with the level of suitability of land for cocoa plants.The results showed that: There were 1) differences in the texture of the ground effect, effective soil depth, drainage, pH, organic matter and slope. At every land unit that is in Nagari Sibakur, there are inhibiting factor and supporting factors to resultfor cocoa crop 2) The presence of the suitability of land for crop diversity cocoa (chocolate coffee) in Nagari Tanjung Gadang Â district of Sijunjung regency. Land units with very suitable conditions for cocoa crops (coffee brown) are in units of the natural levee landform plains (V2) with land units V2.II.kc.g.Pod, (V3) slope foothills V3.III.kc.g . Pod, fluvial plains (F2) F2.II.kc.Pkcs.Pod, (F3) F3.III.kc.Pkcs.Pod alluvial terraces.